2021
DOI: 10.3390/ma14061569
|View full text |Cite
|
Sign up to set email alerts
|

The Relation between Concrete, Mortar and Paste Scale Early Age Properties

Abstract: Microstructure development of concrete, mortar, and paste scale of cement-based material (CBM) during the early hydration stage has a significant impact on CBM’s physical, mechanical, and durability characteristics at the high maturity state. The research was carried out using compositions with increased autogenous shrinkage and extended early age period, proposed within the RRT+ programme of the COST Action TU1404. The electrical conductivity method, used to follow the solidification process of CBM, is capabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…It can also be observed that alkali-activated GGBFS reaches strengths above the 32.5 strength class prescribed in the EN197-1 standard [32], whereas alkali-activated metakaolin has lower strengths than the required by EN standards. Nevertheless, it has to be noted that the EN standard is based on mortars and concretes and it has been reported that the compressive strength of cement pastes increases 30-35% when fine and coarse aggregates are added [33]. Thereafter, one-part and twopart mixes present similar strength development up to 3 days of curing in both systems, and then two-part mix seems to reach higher compressive strengths.…”
Section: Compressive Strengthmentioning
confidence: 98%
“…It can also be observed that alkali-activated GGBFS reaches strengths above the 32.5 strength class prescribed in the EN197-1 standard [32], whereas alkali-activated metakaolin has lower strengths than the required by EN standards. Nevertheless, it has to be noted that the EN standard is based on mortars and concretes and it has been reported that the compressive strength of cement pastes increases 30-35% when fine and coarse aggregates are added [33]. Thereafter, one-part and twopart mixes present similar strength development up to 3 days of curing in both systems, and then two-part mix seems to reach higher compressive strengths.…”
Section: Compressive Strengthmentioning
confidence: 98%
“…The cracks observed in the structures are the final result of a more complex process of the formation and development of damage in early age concrete [ 24 ]. When hardening, concrete reduces its volume due to moisture loss and chemical processes, referred to as shrinkage.…”
Section: Introductionmentioning
confidence: 99%
“…The mortar has been improved by using different polymeric materials to be suitable for the most construction purpose. Many studies were conducted on concrete mixtures to be improved by using polymeric materials to produce polymer modified concrete that gave better workability , higher mechanical properties [3] , modulus of elasticity [3][4][5][6][7][8][9], improve the adhesion strength and permeability resistant [4,[10][11][12], improve water resistance [13][14][15], high resistance to moisture [16], low rate of shrinkage [17] well strength [18][19][20][21] of the reinforced concrete structures but exhibit a limited value of tensile strength for concrete [22].The benefits of improving polymer concrete mixtures is based on increasing the hydration rate reaction and to fill the voids between molecular particles and cement in a regular manner that leads to raise the improved efficiency. Many researches were performed to improve the concrete properties such as; Son and Yeon [25] concluded that with increasing polymer content, elasticity of concrete increased.…”
mentioning
confidence: 99%
“…Shaker and others [26] demonstrated that the use of polymer as proportion of cement mass 15 % improves many properties of concrete, such as water poverty due to loss, corrosion resistance , sulfate resistance , and protection of reinforcing steel from corrosion. SBR, EVA and acrylates polymers have been used a lot in improving the physical and chemical properties of concrete [10,11,[27][28][29][30], but sometimes it is less flexible [11,12,31]. Pei et al [32] concluded that polymer modified concrete has weak mechanical properties.…”
mentioning
confidence: 99%